Effects of boron and nitrogen doping on the electronic properties of graphene-based heterostructures with two-dimensional semiconducting materials - Zhiang Liu; Ping Huang; Yi Luo; Pinbo Huang (PLoS ONE, 2026)
Based on first-principles density functional theory (DFT) calculations , heterostructures composed of graphene and two-dimensional semiconducting materials exhibit significant potential for applications in nanoelectronics devices. In this study, we propose an innovative approach to modulate the electronic properties of such heterostructures. We conduct a comprehensive investigation into the structural properties, band structures, and band alignments of ten widely studied two-dimensional semiconducting materials, unveiling opportunities for forming Schottky contacts with graphene. Furthermore, we demonstrate that the work function of graphene can be extensively tuned via boron or nitrogen doping. Our findings reveal that B- or N-doping in graphene substantially modifies the electronic properties of graphene/two-dimensional semiconducting materials heterostructures, enabling transitions between p-type and n-type Schottky contacts and even facilitating a shift from Schottky to Ohmic contacts in some cases. This tunability is critical for the precise design of graphene/two-dimensional semiconducting materials heterostructures with optimized Schottky barrier heights, paving the way for advanced nanoelectronics and catalyst applications.